PENGARUH KEPERCAYAAN, PENGALAMAN PEMBELIAN, DAN KEMUDAHAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SECARA ONLINE - SELVI EKA SARI (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2020)
This study aims to determine the effect of trust, experience and ease of use partially and simultaneously on the decision to purchase products online at Batik Batik University Students in Surakarta. This type of research is quantitative. The population in this study were students of the Faculty of Economics Regular Morning Study Program 7, totaling 300 people. The sampling technique used incidental sampling of 100 respondents. This study uses data analysis techniques in the form of multiple linear regression test. The results of this study indicate that: (1) There is an influence of Trust on Online Product Purchasing Decisions in Students of Surakarta Batik Islamic University (2) There is an influence of Experience on Online Product Purchasing Decisions on Students of Batik Surakarta Islamic University (3) There was no influence of Ease of Use on Online Product Purchasing Decisions of Batik Batik University Students in Surakarta (4) There is a simultaneous influence of Trust, Experience and Ease of Use on Online Purchasing Decisions of Batik Islamic University Students